Domain switching emission from the mixed-mode crack in ferroelectrics by birefringence measurement and phase field modeling. (1st June 2016) - Li, Qun; Pan, Suxin; Liu, Qida; Wang, Jie
Abstract: The spatial and temporal evolution of domain switching near the tip of a mixed-mode crack (e.g., an inclined crack) is observed in ferroelectrics. The birefringence technique is used to measure the optical quantities to demonstrate the domain switching near the crack tip. The results show an intriguing feature that there appears electrical creep and domain switching emission from the crack tip. The actual time-dependence of domain switching emission and its anisotropic velocity is approximately measured. Moreover, the phase field modeling is developed to simulate polarization distribution and domain switching near the crack tip where the time-dependent Ginzburg–Landau equation is used to describe the change of polarization. The phase field results indicate the same features of domain switching emission from the mixed-mode crack. A good agreement between phase field simulation and birefringence measurement is concluded by setting the appropriate kinetic coefficient in the time-dependent Ginzburg–Landau equation.